Intravitreal triamcinolone in subfoveal recurrence of choroidal neovascularisation after laser treatment in macular degeneration. Issue 5 (1st May 2002) - Ranson, N T; Danis, R P; Ciulla, T A; Pratt, L
Abstract : Background: Laser treatment of extrafoveal well delineated choroidal neovascularisation in exudative age related macular degeneration has a high rate of failure with subsequent severe vision loss from subfoveal involvement. Laser treatment may limit scotoma size, but is unpalatable because of early persistent vision loss. Intravitreal triamacinolone injection may be an acceptable alternative therapy in such disparate cases. Methods: 14 consecutive patients with recurrent neovascularisation were treated with a single 4.0 mg injection of triamacinolone and followed for up to 1 year. Visual results were compared with published data from the Macular Photocoagulation Study of recurrent neovascularisation. Results: Mean visual acuity remained stable at about 20/200 throughout the study period in the treated patients. This is comparable to the outcomes in the Macular Photocoagulation Study for laser retreated patients, and better than the observation group. Conclusions: Intravitreal triamcinolone may be an acceptable treatment of subfoveal recurrent neovascularisation while avoiding early persistent vision loss from laser retreatment.